Adipose stromal cells mediated switching of the pro-inflammatory profile of M1-like macrophages is facilitated by PGE2: in vitro evaluation. Issue 7 (July 2017) - Manferdini, C.; Paolella, F.; Gabusi, E.; Gambari, L.; Piacentini, A.; Filardo, G.; Fleury-Cappellesso, S.; Barbero, A.; Murphy, M.; Lisignoli, G.
Summary: Objective: To define if adipose mesenchymal stromal cell (ASC) treatment mediated switching of the pro-inflammatory profile of M1-like macrophages as a means to develop a tailored in vitro efficacy/potency test. Design: We firstly performed immunohistochemical analysis of CD68, CD80 (M1-like) and CD206 (M2-like) macrophages in osteoarthritic (OA) synovial tissue. ASC were co-cultured in contact and in transwell with activated (GM-CSF + IFNγ)-M1 macrophages. We analyzed IL1β, TNFα, IL6, MIP1α/CCL3, S100A8, S100A9, IL10, CD163 and CD206 by qRT-PCR or immunoassays. Prostaglandin E2 (PGE2) blocking experiments were performed using PGE2 receptor antagonist. Results: In moderate grade OA synovium we did not always find a higher percentage of CD80 with respect to CD206. M1-like-activated macrophage factors IL1β, TNFα, IL6, MIP1α/CCL3, S100A8 and S100A9 were down-modulated both in contact and in transwell by ASC. However, in both systems ASC induced the typical M2-like macrophage markers IL10, CD163 and CD206. Activated-M1-like macrophages pre-treated with PGE2 receptor antagonist failed to decrease secretion of TNFα, IL6 and to increase that of IL10, CD163 and CD206 when co-cultured with ASC confirming a PGE2 specific role. Conclusions: We demonstrated that ASC are responsible for the switching of activated-M1-like inflammatory macrophages to a M2-like phenotype, mainly through PGE2. This evidenced that activated-M1-like macrophages may represent a relevant cell model to test the efficacy/potency of ASC and suggests a specific role of ASC as important determinants in therapeutic dampening of synovial inflammation in OA.